About an outcrop with fauna of the venericardia planicosta group in the western burgos province, ne México - Jenchen, Uwe (UANL. Facultad de Ciencias de la Tierra, 2023)
The present study deals with the outcrop “El 7”, which is in the Rio Grande Embayment, western Burgos province, in the "China" district, formed by sedimentary strata from the late Mesozoic and Paleocene. This outcrop is located on the Vaquerías anticline (Higueras-Vaquerías system), known since 1946. Various specimens of the Venericardia planicosta Lamarck group were sampled. After comparing the shell morphology as well as the stratigraphic range of these fossils with holo-, co- and, hypotypes from different publications, a part of the described shells can be assigned to the species Venericardia (Venericor) diga.